TACTICAL ASPECTS IN MANAGING OF RHEUMATIC MITRAL VALVE STENOSIS WITH ATRIAL FIBRILLATION - M.M. Zufarov; V.M. Im; S.K. Khamdamov (Central Asian Journal of Medicine, 2024)
Despite the sufficient level of understanding in the treatment of mitral stenosis, a number of unresolved issues persist. The review article discusses the fundamental strategies in managing patients with rheumatic mitral stenosis complicated by atrial fibrillation. In patients with mitral stenosis, the prevalence of atrial fibrillation ranges from 17% to 60%, depending on age, leading to a fivefold increase in the risk of stroke and a twofold increase in the risk of mortality.